THE FOOD, FECUNDITY AND GONADAL MATURITY OF VALAMUGIL CUNNESIUS (PISCES: MUGILIDAE) IN THE NEGOMBO LAGOON, SRI LANKA - Wijeyaratne, M J S; Costa, H H (Indian Journal of Fisheries, 2011)
Investigations on reproductive biology and feeding of Valamugil cunnesius (Valenciennes) were carried out for a period of two years on the specimens collected fromNegombo lagoon (7Â°10/N and79Â° 50’E) in the west coast of Sri Lanka. V. cunnesius was found to be spawning in March, June, August and December. The percentage of females in the population was about 80 %. The mean lengths at maturity for males and females were 16.9 and 16.0 cm respectively. The absolute fecundity ranged from 80,000 to 1,40,000 for the fish of 15-20 cm in total length. The most important food item was observed to be benthic polychaetes. High overlap in the dietary composition was evident among the individuals of different size groups.